Tissue explants as tools for studying the epigenetic modulation of the GH-IGF-I axis in farmed fish - Perera, Erick; Román-Padilla, Javier; Hidalgo-Pérez, Juan Antonio; Huesa-Cerdán, Rubén; Yúfera, Manuel; Mancera, Juan Miguel; Martos-Sitcha, Juan Antonio; Martínez-Rodríguez, Gonzalo; Ortiz-Delgado, Juan Bosco; Navarro-Guillén, Carmen; Rodriguez-Casariego, Javier A. (Frontiers in Physiology, 2024)
Somatic growth in vertebrates is mainly controlled by the growth hormone (GH) / insulin-like growth factor I (IGF-I) axis. The role of epigenetic mechanisms in regulating this axis in fish is far from being understood. This work aimed to optimize and evaluate the use of short-term culture of pituitary and liver explants from a farmed fish, the gilthead seabream Sparus aurata, for studying epigenetic mechanisms involved in GH/IGF-I axis regulation. Our results on viability, structure, proliferation, and functionality of explants support their use in short-term assays. Pituitary explants showed no variation in gh expression after exposure to the DNA methylation inhibitor decitabine (5-Aza-2'-deoxycytidine; DAC), despite responding to DAC by changing dnmt3bb and tet1 expression, and TET activity, producing an increase in overall DNA hydroxymethylation. Conversely, in liver explants, DAC had no effects on dnmts and tets expression or activity, but modified the expression of genes from the GH-IGF-I axis. In particular, the expression of igfbp2a was increased and that of igfbp4, ghri and ghrii was decreased by DAC as well as by genistein, which is suggestive of impaired growth. While incubation of liver explants with S-adenosylmethionine (SAM) produced no clear effects, it is proposed that nutrients must ensure the methylation milieu within the liver in the fish to sustain proper growth, which need further in vivo verification. Pituitary and liver explants from S. aurata can be further used as described herein for the screening of inhibitors or activators of epigenetic regulators, as well as for assessing epigenetic mechanisms behind GH-IGF-I variation in farmed fish.